Association of \(FSIP2\) rs4666689 and \(PON2\) rs7493 with male infertility in Vietnamese population - Huu Dinh, Tran; Thanh Thao, Dinh; Lan Anh, Luong Thi; Minh Duc, Bui; Thuy Duong, Nguyen (Academia Journal of Biology, 2021)
Reproductive impairment in men is a multifactorial disease and is currently considered a global health issue. Previous studies have investigated the correlation between genetic variants and male infertility in different populations. However, such studies have appeared in limited amounts in the Vietnamese population. This study aimed to assess the association of polymorphisms FSIP2 rs4666689 and PON2 rs7493 with male infertile susceptibility in the Vietnamese population. Total DNAs were isolated from 376 samples, including 175 males with infertility and 201 controls having at least one child. For FSIP2 rs4666689, all 376 samples were applied for genotyping using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). For PON2 rs7493, only 178 samples (80 infertile patients and 98 controls) were used to assess genotype frequencies. By using statistical methods, we showed that the distribution of their genotypes was in accordance with Hardy-Weinberg equilibrium (p-values > 0.05). However, no association between both polymorphisms (FSIP2 rs4666689 and PON2 rs7493) and male infertility in the Vietnamese population was detected (p-values > 0.05). This study would help enrich to the knowledge about the effects of hereditary factors on male infertility in the Vietnamese population.